2019
DOI: 10.1007/s00401-019-02020-0
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation molecular subgrouping of medulloblastoma: an international meta-analysis of Group 3 and Group 4 subtypes

Abstract: In 2012, an international consensus paper reported that medulloblastoma comprises four molecular subgroups (WNT, SHH, Group 3, and Group 4), each associated with distinct genomic features and clinical behavior. Independently, multiple recent reports have defined further intra-subgroup heterogeneity in the form of biologically and clinically relevant subtypes. However, owing to differences in patient cohorts and analytical methods, estimates of subtype number and definition have been inconsistent, especially wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
283
3
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(305 citation statements)
references
References 31 publications
9
283
3
10
Order By: Relevance
“…For the clinically and biologically heterogeneous Group 3 and Group 4 MB several cohorts were recently combined and expanded by Sharma et al in an attempt to reconcile the varying proposed systems for sub‐classification. This led to the recognition of eight distinct molecular subtypes largely based on DNA methylation data that showed significant differences in clinical presentation, cytogenetics, age of incidence, and/or survival outcomes . Findings such as these support the genetic and epigenetic overlap between consensus Group 3 and Group 4 tumours previously shown by DNA methylation and more recently by single‐cell transcriptomics .…”
Section: Methylation Profiling Of Established Paediatric Brain Tumourmentioning
confidence: 75%
See 1 more Smart Citation
“…For the clinically and biologically heterogeneous Group 3 and Group 4 MB several cohorts were recently combined and expanded by Sharma et al in an attempt to reconcile the varying proposed systems for sub‐classification. This led to the recognition of eight distinct molecular subtypes largely based on DNA methylation data that showed significant differences in clinical presentation, cytogenetics, age of incidence, and/or survival outcomes . Findings such as these support the genetic and epigenetic overlap between consensus Group 3 and Group 4 tumours previously shown by DNA methylation and more recently by single‐cell transcriptomics .…”
Section: Methylation Profiling Of Established Paediatric Brain Tumourmentioning
confidence: 75%
“…Classifiers evolve by increasing the number of samples in the reference cohort and the number of distinct methylation classes. Some classifiers attempt to classify a sample into broad diagnostic categories/entities reminiscent of current traditional classifications whereas other classifiers are specialized on the sub‐classification of specific entities . The relatively small, easily exchangeable and highly standardized methylation array data seems like the perfect fuel for the newly ignited fire of machine‐learning‐based cancer classification.…”
Section: The Development Of Dna Methylation‐based Brain Tumour Classimentioning
confidence: 99%
“…Based primarily on DNA methylation analysis, medulloblastoma is known to be a heterogeneous disease comprising four distinct molecular subgroups (WNT, SHH, G3, and G4) with significant differences in their clinical and pathologic characteristics, genetic drivers of disease development and progression patterns, and clinical prognosis [18,[46][47][48]. More recent studies employing additional genomic analyses and patient samples have identified distinct subtypes within each of these molecular subgroups [19,[49][50][51]. These data have already informed clinical trial design, with the incorporation of molecular profiling to help guide dose de-escalation in WNT medulloblastoma and intensify therapy in G3 medulloblastoma.…”
Section: Towards Subgroup-specific Radiotherapy Guidelinesmentioning
confidence: 99%
“…Thus, efforts have been directed toward maintaining or improving overall survival rates while minimizing treatment-related toxicity. These efforts have primarily focused on modifications to RT approaches that can be broadly grouped as follows: investigations of the effects of adding concurrent and/or adjuvant chemotherapy regimens [9,10]; investigations of the effects of delaying or omitting RT for very young children [11][12][13][14]; investigations of the effects of reductions in the RT dose and field size [15,16]; and, over the past decade, the identification of distinct molecular subgroups of medulloblastoma with specific alterations that drive tumorigenesis, facilitating the identification of new therapeutic targets and enhanced risk stratification [17][18][19].…”
mentioning
confidence: 99%
“…27 Lately, further molecular subgrouping can define the prognosis even better. 28 In the past, infant with medulloblastoma is considered as having poor prognosis with the exception of those with desmoplastic histology. It was speculated that it is due to the avoidance or delay of irradiation accounting for such adverse outcome.…”
Section: Medulloblastoma With Variable Genetic Mutationsmentioning
confidence: 99%